Nominale Determination im Bulgarischen und Mazedonischen - Sachliyan, Syuzan (2021)
Bulgarian and Macedonian are the only Slavic languages with definite and indefinite articles. Macedonian is among the few languages that differentiate the definite article deictically. This innovative study presents a complete semantic analysis of nominal determination in both languages, including article-less nominal phrases.